Effect of PAK Inhibition on Cell Mechanics Depends on Rac1 - Mierke, Claudia Tanja; Puder, Stefanie; Aermes, Christian; Fischer, Tony; Kunschmann, Tom (Frontiers in Cell and Developmental Biology, 2020)
Besides biochemical and molecular regulation, the migration and invasion of cells is controlled by the environmental mechanics and cellular mechanics. Hence, the mechanical phenotype of cells, such as fibroblasts, seems to be crucial for the migratory capacity in confined 3D extracellular matrices. Recently, we have shown that the migratory and invasive capacity of mouse embryonic fibroblasts depends on the expression of the Rho-GTPase Rac1, similarly it has been demonstrated that the Rho-GTPase Cdc42 affects cell motility. The p21-activated kinase (PAK) is an effector down-stream target of both Rho-GTPases Rac1 and Cdc42, and it can activate via the LIM kinase-1 its down-stream target cofilin and subsequently support the cell migration and invasion through the polymerization of actin filaments. Since Rac1 deficient cells become mechanically softer than controls, we investigated the effect of PAK I group and PAK1 inhibition on cell mechanics in the presence and absence of Rac1. Therefore, we determined whether mouse embryonic fibroblasts, in which Rac1 was knocked-out, and control cells, displayed cell mechanical alterations after treatment with group I PAKs or PAK1 inhibition using a magnetic tweezer (adhesive cell state) and an optical cell stretcher (non-adhesive cell state). In fact, we found that group I PAKs and Pak1 inhibition decreased the stiffness and the Young’s modulus of fibroblasts in the presence of Rac1 independent of their adhesive state. However, in the absence of Rac1 the effect was abolished in the adhesive cell state for both inhibitors and in their non-adhesive state, the effect was abolished for the FRAX597 inhibitor, but not for the IPA3 inhibitor. The migration and invasion were additionally reduced by both PAK inhibitors in the presence of Rac1. In the absence of Rac1, only FRAX597 inhibitor reduced their invasiveness, whereas IPA3 had no effect. These findings indicate that group I PAKs and PAK1 inhibition is solely possible in the presence of Rac1 highlighting Rac1/PAK I (PAK1, 2 and 3) as major players in cell mechanics.